amidoamine composition and adhesive composition containing the same

KR103031494B1Active Publication Date: 2026-10-13EVONIK OPERATIONS GMBH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020237043079
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-14
Publication Date
2026-10-13
Estimated Expiration
2041-05-14

Smart Images

  • Figure 112023139623036-PCT00002
    Figure 112023139623036-PCT00002
  • Figure 112023139623036-PCT00004
    Figure 112023139623036-PCT00004
  • Figure 112023139623036-PCT00006
    Figure 112023139623036-PCT00006
Patent Text Reader

Abstract

An amidoamine composition, an adhesive composition comprising the amidoamine composition, and a method for preparing the amidoamine composition are provided. The amidoamine composition contains polyamidoamine and an ammonium salt of aminosilane or mercaptosilane.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to an amidoamine composition, an adhesive composition containing the same, and a method for preparing an amidoamine composition. Background Technology

[0002] Due to stricter environmental regulations, particularly those related to controlling volatile organic compound (VOC) emissions and achieving carbon neutrality, there is high demand for new energy vehicles, especially electric vehicles (EVs). To achieve high range for a given battery size and weight, weight reduction in EVs is required. Currently, aluminum is the preferred material among engineers and designers. Within various EVs, lightweight aluminum alloys are candidates to replace carbon steel with cathode electrode deposition (CED) coatings to save energy and improve corrosion resistance. In the absence of CED coatings, it is very difficult for conventional polyvinyl chloride (PVC) plastisols to bond directly to the surface of aluminum alloys. Consequently, there is high demand for coatings and adhesives capable of strongly bonding to the surface of aluminum alloy parts.

[0003] The following disclosed patent application discloses an epoxy 2K (2-component) composition and its excellent adhesion to aluminum alloy surfaces for adhesive or ink coating applications.

[0004] Published Patent Application 1: EP3317329A1

[0005] Published Patent Application 2: EP1885764A1

[0006] The present disclosure provides an amidoamine composition, which, after being mixed with a PVC plastisol or epoxy resin, can achieve improved adhesion to a metal surface. Additionally, an adhesive composition containing the amidoamine composition, as well as a method for preparing the amidoamine composition, are provided.

[0007] summation

[0008] One object of the present disclosure is to provide an amidoamine composition capable of achieving strong adhesion to a metal surface, such as an aluminum alloy surface, when combined with a curable polymeric composition.

[0009] This object of the present disclosure is: i) a) at least one amide group or at least one imide group; and b) an amidoamine having at least one amino group; and ii) c) an ammonium salt of an aminosilane represented by formula (I):

[0010] ,

[0011] and d) mercaptosilane represented by chemical formula (II):

[0012]

[0013] This is achieved by providing an amidoamine composition comprising one or more silanes selected from the group consisting of,

[0014] Here, R1 is a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group; R2 and R2' are independently aliphatic chains having at least one carbon atom; and R3, R3', R4, R4', R5 and R5' are independently an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms.

[0015] Preferably, R1 has at least one nitrogen atom of the form -NH2, -NHR6, or -NR7R8, where R6, R7, and R8 is independently an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group.

[0016] Preferably, R3, R3', R4, R4', R5, and R5' are independently selected from methyl, ethyl, propyl, butyl, methoxy, ethoxy, propoxy, butoxy, or 2-(2-butoxyethoxy)ethoxy.

[0017] Preferably, amidoamine is a reaction product of a) one or more carboxylic acids and b) one or more amines having at least two amino groups.

[0018] Preferably, the carboxylic acid includes a dicarboxylic acid.

[0019] Preferably, the amine comprises one or more polyalkylene polyamines.

[0020] Preferably, amidoamine is a reaction product of a) one or more amines having a terminal primary amino group and b) one or more copolymers of an alpha-olefin and an unsaturated carboxylic acid anhydride.

[0021] Preferably, the amine comprises one or more selected from aminomethylpiperazine, aminoethylpiperazine, aminopropylpiperazine, aminomethylimidazolidine, aminoethylimidazolidine, aminopropylimidazolidine, dimethylaminopropylamine, or dimethylaminopropylaminopropylamine.

[0022] Preferably, the alpha-olefin is an alpha-olefin having 2 to 20 carbon atoms.

[0023] Preferably, the unsaturated carboxylic acid anhydride is selected from maleic anhydride, itaconic anhydride, or citraconic anhydride.

[0024] Preferably, the amidoamine composition further comprises an organic chloride.

[0025] Another objective of the present disclosure is achieved by providing an adhesive composition comprising: 1) an amidoamine composition; and 2) a curable polymeric composition.

[0026] Preferably, the curable polymeric composition comprises poly(vinyl chloride) or vinyl chloride copolymer.

[0027] Preferably, the curable polymeric composition includes an epoxy polymer.

[0028] Preferably, the adhesive composition further includes a plasticizer.

[0029] Preferably, the adhesive composition further comprises one or more additives selected from fillers, reinforcing agents, adhesion promoters, tougheners, defoaming agents, dispersants, lubricants, colorants, marking materials, dyes, pigments, IR absorbers, antistatic agents, anti-blocking agents, nucleating agents, crystallization accelerators, crystallization retardants, conductive additives, carbon black, graphite, carbon nanotubes, graphene, drying agents, release agents, leveling aids, flame retardants, separators, optical whitening agents, rheology additives, photochromic additives, softeners, anti-slip agents, stabilizers, metal glitter, metal-coated particles, porosity inducers, glass fibers, nanoparticles, flow aids, or combinations thereof.

[0030] Preferably, the additive has a weight percentage of less than 90% based on the total weight of the adhesive composition.

[0031] Preferably, the amidoamine composition has a weight percentage of less than 10% based on the total weight of the adhesive composition.

[0032] Preferably, the amidoamine composition has a weight percentage of more than 0.5% and less than 5% based on the total weight of the adhesive composition.

[0033] Another object of the present disclosure is: i) providing an amidoamine having at least one amide group and b) at least one amino group; ii) c) an ammonium salt of an aminosilane represented by formula (I);

[0034] , and

[0035] d) Mercaptosilane represented by chemical formula (II):

[0036]

[0037] A step of providing one or more silanes selected from the group consisting of

[0038] This is achieved by providing a method for preparing an amidoamine composition, comprising the step of mixing amidoamine and one or more silanes to form an amidoamine composition, wherein R1 is a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group; R2 and R2' are independently aliphatic chains having at least one carbon atom; and R3, R3', R4, R4', R5, and R5' are independently an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms.

[0039] The composition of the present disclosure provides a PVC plastisol or epoxy system having excellent properties of strong bonding to metal surfaces, which is suitable for many applications in electric vehicles. Specific details for implementing the invention

[0040] The following description is for illustrative purposes only and does not limit the scope of the disclosure.

[0041] The term "amidoamine" refers to a series of organic compounds containing at least one amido or imido group in addition to at least one amino group in the skeleton. The amino groups are primary amino groups -NH2 and secondary amino groups -NHR. A , or tertiary amino group -NR B R C It can be, where R A , R B , and R CIt is an independent hydrocarbon radical group. Amidoamine can serve as a curing agent for various polymeric compositions, for example, epoxy resins.

[0042] The term "mercaptosilane" refers to a series of silanes having at least one mercapto group attached directly or indirectly to a silicon atom through a carbon chain. Conventionally, mercaptosilanes are widely used as coupling agents for silica-based materials due to their difunctional nature. Without limitation, known mercaptosilanes include (3-mercaptopropyl)-triethoxysilane and (3-mercaptopropyl)trimethoxysilane.

[0043] The term "aminosilane" refers to a series of silanes having at least one amino group attached directly or indirectly to a silicon atom through a carbon chain. Conventionally, aminosilanes are widely used as coupling agents for silica-based materials due to their difunctional nature. Known aminosilanes, without limitation, include (3-aminopropyl)-triethoxysilane, (3-aminopropyl)-diethoxy-methylsilane, (3-aminopropyl)-dimethyl-ethoxysilane, (3-aminopropyl)-trimethoxysilane, (3-(aminoethylamino)propyl)-trimethoxysilane, (3-(aminoethylamino)propyl)-methyldimethoxysilane, and (3-(aminoethylamino)propyl)-triethoxysilane.

[0044] As used herein, the term "plastizol" refers to a suspension of polyvinyl chloride (PVC) or other polymer particles in a liquid plasticizer. Plastisols flow as liquids and can be poured into a heated mold. When heated to a specific temperature or temperature range, the plastic particles dissolve, and the mixture transforms into a high-viscosity gel that can no longer be poured. Plastisols are commonly used as coatings.

[0045] amidoamine

[0046] According to the present disclosure, amidoamine has at least one amido or imido group and at least one amino group. Amidoamine can be prepared by reacting a carboxylic acid with at least one amine having at least two amino groups. Alternatively, amidoamine can be prepared by reacting an anhydride-based copolymer with at least one amine having a terminal primary amino group.

[0047] The reaction can be carried out in a non-aqueous medium at an elevated temperature. A mixture of a carboxylic acid and / or anhydride and a polyamine is preferably vigorously stirred to achieve a homogeneous distribution of the reactants. An inert atmosphere is preferably applied to prevent or inhibit oxidation or side reactions. After condensation for several hours, evaporation is performed to remove water, which is one of the reaction products.

[0048] The stoichiometric ratio of the carboxyl groups of carboxylic acids and / or carboxylic acid anhydrides to the amino groups of polyamines is such that almost all carboxyl and anhydride groups are consumed, while a significant amount of amino groups remain unreacted. Among the resulting products, unreacted amino groups are essential for promoting adhesion of polymeric compositions, including PVC plastisols or epoxy resins, to metal surfaces.

[0049] carboxylic acid

[0050] As used herein, the term "carboxylic acid" refers to an organic acid having one or more carboxyl groups. The carboxyl groups may react with the amino groups of amines to form an amido moiety. The carboxylic acid comprises, without limitation, fatty acids, hydrogenated fatty acids, dimeric fatty acids, hydrogenation products of dimeric fatty acids, trimerized fatty acids, hydrogenation products of trimerized fatty acids, or combinations thereof. Preferably, the carboxylic acid comprises at least one dicarboxylic acid. More preferably, the dicarboxylic acid comprises a dimeric fatty acid or a hydrogenated dimeric fatty acid. Even more preferably, the dimeric fatty acid or hydrogenated dimeric fatty acid has 24 to 48 carbon atoms.

[0051] Anhydride-based copolymer

[0052] Amidoamines can be prepared by reacting an anhydride-based copolymer with a polyamine having a terminal primary amino group. Anhydride-based copolymers refer to a group of copolymers prepared by polymerizing an unsaturated monomer with an unsaturated anhydride. Anhydride-based copolymers contain a reactive anhydride moiety, which can react with an amine to form a condensate containing an imido group.

[0053] Preferably, the unsaturated monomer contains at least one ethylenically unsaturated bond. More preferably, the unsaturated monomer is selected from alpha-olefin, (meth)acrylate, (meth)acrylamide, (meth)acrylonitrile, or any combination thereof.

[0054] More preferably, the alpha-olefin comprises an alpha-olefin having 2 to 20 carbon atoms. Exemplary alpha-olefins include ethylene, propylene, 1-butylene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, or 1-octadecene.

[0055] The unsaturated carboxylic acid anhydride is an anhydride of an unsaturated dicarboxylic acid. Preferably, the unsaturated carboxylic acid anhydride is one or more selected from maleic anhydride, itaconic anhydride, or citraconic anhydride.

[0056] Exemplary anhydride-based copolymers include polyethylene-graft-maleic anhydride, maleic anhydride-graft polypropylene, styrene-maleic anhydride copolymer, maleic anhydride-methyl methacrylate copolymer, or maleic anhydride-acrylamide copolymer.

[0057] amine

[0058] In the present disclosure, the amines for producing amidoamines include various diamines, triamines, tetraamines, or any combination thereof. Diamines include non-cyclic or cyclic diamines without limitation. Non-cyclic diamines include polyalkylamines and polyetheramines without limitation. Cyclic diamines include alicyclic amines, aromatic amines, and amino-containing heterocycles without limitation.

[0059] Exemplary polyalkylamines are known, for example, ethyleneamines, propyleneamines, or substituted ethyleneamines such as ethylenediamine (EDA), diethylenetriamine (DETA), triethylenetetraamine (TETA), tetraethylenepentaamine (TEPA), pentaethylenehexaamine (PEHA), N,N'-bis(3-aminopropyl)ethylenediamine, N,N"-bis(3-aminopropyl)diethylenetriamine, tris(2-aminoethyl)amine, aminoethylpiperazine, dipropylenetriamine, and tripropylenetetraamine.

[0060] Polyetheramines are also known as poly(oxyalkylene) polyamines or amine-terminated polyethers. Exemplary polyetheramines are known to be based, for example, ethylene glycol, propylene glycol, glycerol, pentaerythritol, or combinations thereof. Commercially available polyetheramines can be purchased from various manufacturers, for example, as the JEFFAMINE® D series from Huntsman Corporation.

[0061] Exemplary alicyclic amines are diamines or triamines having an amino group directly or indirectly bonded to a non-aromatic carbon ring system. Commercially available alicyclic amines include, without limitation, isomers of diaminocyclohexane, isomers of bis(aminomethyl)cyclohexane, 4,4'-methylenebiscyclohexaneamine, bis(aminomethyl)norbornane, and isophorone diamine.

[0062] Exemplary aromatic amines are diamines or triamines having an amino group directly or indirectly bonded to an aromatic ring system. Commercially available aromatic amines include, without limitation, isomers of phenylenediamine, isomers of xylylenediamine, isomers of methylenedianiline, and 1,1'-biphenyl-4,4'-diamine.

[0063] Amino-containing heterocycles are known to have, for example, aminoalkyl groups attached to nitrogen-containing heterocycles. Nitrogen-containing heterocycles include, without limitation, aziridine, azetidine, pyrrolidine, pyrrole, piperidine, azephan, azepine, azocan, azonan, azonin, diaziridine, diazetidine, imidazolidine, imidazole, pyrazolidine, pyrazol, triazole, diazinan, diazine, and triazinan. An aminoalkyl group refers to a saturated hydrocarbon radical having at least one hydrogen atom substituted by a primary, secondary, or tertiary amino group. Exemplary amino-containing heterocycles include, without limitation, aminomethylpiperazine, aminoethylpiperazine, aminopropylpiperazine, aminomethylimidazolidine, aminoethylimidazolidine, or aminopropylimidazolidine.

[0064] Silan

[0065] The amidoamine composition provided in the present disclosure is a) an ammonium salt of an aminosilane represented by the formula (I):

[0066] ,

[0067] and b) mercaptosilane represented by chemical formula (II):

[0068]

[0069] It additionally includes one or more silanes selected from the group consisting of,

[0070] Here, R1 is a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group; R2 and R2' are independently aliphatic chains having at least one carbon atom; and R3, R3', R4, R4', R5, and R5' are independently a hydrocarbon radical having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms.

[0071] The hydrocarbon radical may be an alkyl, alkenyl, alkynyl, or aryl group. Preferably, the hydrocarbon radical is methyl, ethyl, propyl, butyl, pentyl, hexyl, cyclohexyl; vinyl, allyl; ethinyl; phenyl, tolyl, benzyl, 2-phenylethyl, xylyl, or naphthyl.

[0072] An alkoxy or aryloxy group refers to an organic group formed by removing a hydrogen atom from an alcohol or phenolic hydroxyl group (-OH).

[0073] The alcohol may be a monohydroxy alcohol, e.g., methanol, ethanol, propanol, butanol, 2-methoxyethanol, 2-ethoxyethanol; a dihydroxy alcohol, e.g., ethylene glycol, propylene glycol, polyethylene glycol; a trihydroxy alcohol, e.g., glycerol; or a polyhydroxy alcohol having four or more hydroxyl groups. Preferably, the alkoxy group is a group derived from methoxy, ethoxy, propoxy, butoxy, or a glycol monoether. The glycol monoether is an alkyl / aryl ether of glycol, usually ethylene glycol or propylene glycol. Commonly used glycol monoethers may include, without limitation, 2-methoxyethanol, 2-ethoxyethanol, 2-propoxyethanol, 2-phenoxyethanol, 1-methoxy-2-propanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether (also known as butyl diglycol), dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, ethoxylated C12 alcohol, ethoxylated C13 alcohol, ethoxylated C14 alcohol, or ethoxylated C15 alcohol.

[0074] The phenolic group may be phenol, 4-nonylphenol, xylenol, or bisphenol A. Preferably, the aryloxy group is a phenoxy or aryloxy group.

[0075] R3, R3', R4, R4', R5, and R5' are preferably methyl, ethyl, propyl, butyl, methoxy, ethoxy, propoxy, butoxy, or 2-(2-butoxyethoxy)ethoxy.

[0076] Mercapto groups and ammonium cations are known to have excellent reactivity that is important for improving adhesion to metal surfaces.

[0077] Preferably, the silane is a mercaptosilane having at least one mercapto group (-SH). Exemplary mercaptosilanes are known, for example, 3-mercaptopropylmethyldimethoxysilane, (3-mercaptopropyl)trimethoxysilane (MPTMS), and (3-mercaptopropyl)-methyl-dimethoxysilane (MPDMS).

[0078] Preferably, the silane is an ammonium salt of aminosilane.

[0079] Preferably, in the ammonium salt of an aminosilane, R1 is a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group.

[0080] Preferably, the radical R1 of the aminosilane may have at least one nitrogen atom. The nitrogen atom exists in the form of -NH2, -NHR6, or -NR7R8, where R6, R7, and R8 is independently an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group. In this case, the aminosilane has at least two amino groups.

[0081] The ammonium salt may be an ammonium salt of any acid known to a person skilled in the art. Preferably, the ammonium salt is a sulfate, bisulfate, nitrate, perchlorate, phosphate, fluoride, chloride, bromide, iodide, formate, acetate, oxalate, benzoate, etc.

[0082] Ammonium salts of aminosilanes can be prepared by synthetic approaches known to those skilled in the art. As an example, the hydrochloride of an aminosilane having the aminosilane represented by formula (II) in this disclosure was prepared by reacting a chlorohydrocarbon represented by formula (III) with an aminosilane represented by formula (IV).

[0083]

[0084] Here, R1 is a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group; R2 is an aliphatic chain having at least two carbon atoms; and R3, R4, and R5 are independently a hydrocarbon radical having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms.

[0085] Organic chloride

[0086] In some embodiments, in addition to amidoamine and silane containing unreacted amino groups, the amidoamine composition may further comprise at least one organic chloride. The organic chloride is preferably an alkyl chloride, alkenyl chloride, alkynyl chloride, or aryl chloride, including, without limitation, chloromethane, chloroethane, chloropropane, benzyl chloride, vinylbenzyl chloride, and xylylene dichloride.

[0087] Organic chlorides may be added to the amidoamine composition in any suitable order. In some embodiments, organic chlorides were added to freshly prepared amidoamine to form a mixture. Then, silane was added to the mixture.

[0088] Adhesive composition

[0089] The amidoamine compositions provided in the present disclosure can be used as coupling agents or adhesion promoters in adhesive compositions, particularly those based on PVC plastisol or epoxy resin.

[0090] In the adhesive composition, the amidoamine composition has a weight percentage of preferably less than 10%, more preferably greater than 0.5% to less than 8%, and even more preferably greater than 1% to less than 4% based on the total weight of the adhesive composition.

[0091] In addition to the amidoamine compositions provided in the present disclosure, the adhesive composition may include one or more curable polymeric compositions. A detailed description of the curable polymeric compositions is provided below.

[0092] Curable polymeric composition

[0093] The adhesive composition comprises a curable polymeric composition, which may be vulcanized or hardened upon exposure to certain factors, such as moisture, light, heat, or a curing agent. The curable polymeric composition preferably comprises poly(vinyl chloride), vinyl chloride copolymer, or epoxy polymer. Although the term "polymeric" is used herein, the term "curable polymeric composition" may refer to a prepolymer or oligomer insofar as they can be polymerized or copolymerized to form a cured / hardened material.

[0094] Vinyl chloride copolymers are a series of copolymers having vinyl chloride as a monomer. The comonomer may be based on olefins, vinyl, (meth)acrylate, or derivatives thereof. Generally known copolymers include copolymers of vinyl chloride and ethylene, propylene, styrene, vinyl acetate, vinyl alcohol, methyl (meth)acrylate, (meth)acrylamide, acrylonitrile, etc.

[0095] The epoxy polymers used herein are a family of polymers, prepolymers, and oligomers having at least one epoxide group. Commercially available epoxy polymers are well known and can be purchased from various manufacturers under the brand names Epon™, Epikure™, and Epikote™ from Hexion Inc., and DER™ and DEN™ from Olin Corporation.

[0096] Other ingredients

[0097] The adhesive composition may include additional components in addition to the amidoamine composition and curable polymeric composition provided in the present disclosure.

[0098] In some aspects of the present disclosure, a plasticizer is included in the adhesive composition. The plasticizer may be present in the PVC plastisol together with poly(vinyl chloride) / vinyl chloride copolymer particles or in the epoxy resin together with the epoxy polymer. The plasticizer may be introduced by mixing the PVC plastisol / epoxy resin with the amidoamine composition of the present disclosure. Alternatively, the plasticizer may be added separately. When various types of plasticizers are used, they are preferably derived from different classes of compounds. Suitable plasticizers are all those commonly used for PVC. The plasticizer is preferably selected from the group consisting of phenolic esters, adipic acid esters, and butyric acid esters.

[0099] The amount of plasticizer in the adhesive composition of the present disclosure can vary widely and is guided by the plasticizing effect on curable polymeric compositions, particularly PVC, vinyl chloride copolymers, or epoxy resins, depending on the requirements when in water. In each case, the amount is preferably 10% to 60% by weight, more preferably 15% to 50% by weight, and particularly 20% to 40% by weight, based on the total amount of the adhesive composition.

[0100] To bring about more functionality or characteristics to satisfy industrial requirements, adhesive compositions preferably include additives. Additives are understood to mean substances added to alter the properties of the adhesive composition in an intended direction to match, for example, viscosity, wetting characteristics, stability, reaction rate, blister formation, storage stability, or adhesion and usage characteristics to the end application. Several additives are described, for example, in WO 99 / 55772, pp. 15-25.

[0101] Desired additives are selected from the group consisting of fillers, reinforcing agents, coupling agents, toughening agents, defoaming agents, dispersing agents, lubricants, coloring agents, marking materials, dyes, pigments, IR absorbers, antistatic agents, anti-blocking agents, nucleating agents, crystallization accelerators, crystallization retardants, conductive additives, carbon black, graphite, carbon nanotubes, graphene, drying agents, release agents, leveling aids, flame retardants, separators, optical whitening agents, rheology additives, photochromic additives, softeners, adhesion promoters, anti-slip agents, metallic pigments, stabilizers, metal glitter, metal-coated particles, porosity inducers, glass fibers, nanoparticles, flow aids, or combinations thereof.

[0102] The additive preferably constitutes a proportion of 90% by weight or less, preferably 70% by weight or less, more preferably 50% by weight or less, and even more preferably 30% by weight or less, based on the total weight of the adhesive composition.

[0103] For example, it is advantageous to add a light stabilizer, for example, a sterically hindered amine, or other auxiliary agent as described, in a total amount of, for example, 0.05% to 5% by weight.

[0104] To produce the adhesive composition of the present disclosure, it is additionally possible to add additives, such as leveling agents, such as polysiloxanes. Additionally, further additional components may optionally be present. Additional auxiliary agents and additives used may be chain transfer agents, plasticizers, stabilizers and / or inhibitors.

[0105] In some cases, the adhesive composition preferably comprises an antioxidant additive. The antioxidant may comprise one or more structural units selected from sterically hindered phenols, sulfides, or benzoates. Here, in the sterically hindered phenol, the two ortho-hydrogen atoms are substituted by a compound that is not hydrogen, preferably having at least 1 to 20, particularly preferably 3 to 15 carbon atoms, and is preferably branched. The benzoate also preferably has a substituent that is not hydrogen, preferably having 1 to 20, more preferably 3 to 15 carbon atoms, and is preferably branched, at the ortho position relative to the OH group.

[0106] In another embodiment, if necessary, one or more catalysts are preferably introduced into the adhesive composition as part of the curing agent composition to promote the reaction between the epoxide groups of the epoxy resin and the amine groups of the curing agent composition. Useful catalysts that can be introduced into the adhesive composition include Ancamine® products available from Evonik Operations GmbH and products marketed as "accelerators" available from Hundsmann Corporation. One exemplary catalyst is piperazine-based accelerator 399 available from Hundsmann Corporation. When used, this catalyst preferably constitutes 0 to about 10 weight percent of the total adhesive composition.

[0107] Preferably, a curing accelerator may be added to the adhesive composition to increase the speed of the curing process when the adhesive composition is applied to a metal surface. The curing accelerator comprises one or more selected from tris-(dimethylaminomethyl)phenol, benzyl dimethylamine, various isomers of nonylphenol, triethanolamine, or N-(3-aminopropyl)iminodiethanol.

[0108] Depending on the final application or environment in which the adhesive composition is used, other additives or components may be present in the system.

[0109] Preferably, the adhesive composition according to the present disclosure comprises the specified components.

[0110] The amidoamine compositions provided in the present disclosure can be found for use in many other fields, including, without limitation, coatings, surface paints, protective films, sealants, fillers, acoustic insulating materials, etc., in addition to adhesives.

[0111] The present disclosure is illustrated by the following examples.

[0112] Examples

[0113] In the following examples, the following materials were used.

[0114] Ancarmin® 2655 was an aliphatic polyamine from Evonik (Shanghai) Specialty Chemicals Co., Ltd.

[0115] Huntsmann Corporation's Zepamin® D230 and Zepamin® D400 were diamines having an oxypropylene moiety. Huntsmann Corporation's Zepamin® T403 was a triamine having an oxypropylene moiety.

[0116] Ankamin® TEPA was Tetraethylenepentaamine (TEPA) of Evonik (Shanghai) Specialty Chemicals Co., Ltd.

[0117] Ankamin® TETA was tetraethylenetetraamine (TETA) of Evonik (Shanghai) Specialty Chemicals Co., Ltd.

[0118] 2-(2-butoxyethoxy)ethanol (DGBE) was of Eastman (China) Co., Ltd.

[0119] The dimeric acid was of Yihai Yuanda (Lianyungang) Co. Ltd.

[0120] Silane 1 was the reaction product of 3-(triethoxysilyl)propanethiol and ethoxylated C13 alcohol of Evonik (Shanghai) Specialty Chemicals Co., Ltd. Silane 2 was the hydrochloride of aminosilane of Evonik (Shanghai) Specialty Chemicals Co., Ltd. Silane 3 was the mercaptosilane of Evonik (Shanghai) Specialty Chemicals Co., Ltd.

[0121] Vinylbenzyl chloride was from Wuhan Organic Industry Co., Ltd.

[0122] Exxsol™ D80 was a dearomatic aliphatic hydrocarbon solvent from ExxonMobil Chemical.

[0123] Diisopropyl naphthalene (DINP) belonged to Bluesail Group Co., Ltd.

[0124] VESTOLIT® P 1353 K was a PVC homopolymer of Vestolit GmbH & Co. KG. VINNOLIT® SA 1062 / 7 was a vinyl chloride / vinyl acetate copolymer of Vinnolit GmbH & Co. KG. Lacovyl® PA 1384 was a vinyl chloride / vinyl acetate copolymer of ARKEMA SA.

[0125] Socal® 312 was a coated chalk from Solvay Chemicals GmbH. Ulmer Weiss XM was a natural chalk from Eduard Merkle GmbH.

[0126] Aerosil® 200 of Evonik Corporation was used as a thixotropic agent.

[0127] CaO in the brand name Precal® 30S of Schaefer Kalk GmbH & Co. KG was a desiccant.

[0128] Zinc oxide from AppliChem GmbH was used as a stabilizer.

[0129] Exxon Mobil Chemical Company's Exol™ D80 was a dearomatic aliphatic hydrocarbon solvent.

[0130] The following protocol was used to test the physical performance or characteristics of the sample:

[0131] Viscosity was measured at 25°C using a Brookfield DV-II+Pro viscometer according to ASTM D445-83. Thin film setting time (TFST) was measured using a Beck-Koller dry recorder according to ASTM D5895.

[0132] The amine value was measured using a Mettler titrator according to ASTM D 2074 (perchloric acid titration).

[0133] Gardner color was measured according to ASTM D 1544-80.

[0134] The manual adhesion test method is as described below.

[0135] PVC plastisol was applied to a clean metal substrate as a continuous ribbon with a length of 8 cm, a width of 15 mm, and a thickness that gradually increased from 0 to 3 mm. The samples were baked in a convection oven based on a baking circle. After baking, the samples were cooled to ambient temperature, and manual adhesion tests were performed twice. The first test was performed 1 hour after the end of baking. The second test was performed 24 hours after the end of baking. The adhesion measurement technique is described as follows. First, two parallel strips were cut at the thickest (3 mm) ends of the plastisol ribbon. The strips were 1.5 cm apart. A scraper was inserted under the cut strips to cleanly separate the first 0.5 to 1 cm of the strips from the substrate. Subsequently, the loosely hanging edges of the plastisol strips were pulled off from the substrate. The first strip was pulled quickly, and the second strip was pulled slowly. Passive adhesion was evaluated into three categories based on the degree of force required to pull the plastisol strip from the substrate: excellent adhesion (high force), acceptable adhesion (medium force), or unacceptable adhesion (low force).

[0136] Synthesis procedure

[0137] Example 1

[0138] Synthesis was performed in the following steps.

[0139] Step 1: A 2000 mL 4-neck round-bottom flask was equipped with a vacuum line, a dropping funnel, a nitrogen outlet, and a stirrer. The flask was filled with 460 g of dimeric acid, 102 g of Ancarmine® 2655, and 133 g of tetraethylenepentaamine (TEPA). The mixture was heated to 180°C under stirring to remove water. The temperature was raised to 250°C and the reaction was carried out for 2 hours. Subsequently, the vacuum line was switched on and nitrogen purging was stopped to reduce the pressure. Water was removed. The contents were cooled to 100°C. 60 g of 2-(2-butoxyethoxy)ethanol (DGBE) was added to the mixture. The mixture was stirred for 1 hour and then cooled to 70°C.

[0140] Step 2: 90 g of the reaction product from Step 1 was loaded into a flask and heated to 50°C, after which 10 g of silane 1 in methanol was added dropwise within 30 minutes. The vacuum line was switched on to distill the methanol. The mixture was stirred for 1 hour and then discharged.

[0141] The typical characteristics of this finished product were as follows: viscosity at 40°C 22,102 mPa·s; Gardner color 10; amine value 302 mg KOH / g.

[0142] Example 2

[0143] Step 1: A 2000 mL 4-neck round-bottom flask was equipped with a vacuum line, a dropping funnel, a nitrogen outlet, and a stirrer. The flask was filled with 460 g of dimeric acid, 102.1 g of Ancarmine® 2655, and 133.1 g of tetraethylenepentaamine (TEPA). The mixture was heated to 180°C under stirring to remove water. The temperature was raised to 250°C and the reaction was carried out for 2 hours. Water was removed. Subsequently, the vacuum line was switched on and nitrogen purging was stopped to reduce the pressure. The contents were cooled to 100°C. 100 g of diisopropyl naphthalene (DINP) was added to the mixture. The mixture was stirred for 1 hour and then cooled to 70°C.

[0144] Step 2: 95 g of the reaction product from Step 1 was loaded into a flask and heated to 50°C, after which 10 g of silane 1 in methanol was added dropwise within 30 minutes. The vacuum line switch was turned on. The mixture was stirred for 1 hour and then discharged.

[0145] The typical characteristics of this finished product were as follows: viscosity at 40°C 35,890 mPa·s; Gardner color 12; amine value 286 mg KOH / g.

[0146] Example 3

[0147] Step 1: All synthesis processes are the same as Step 1 of Example 1.

[0148] Step 2: 90 g of the reaction product from Step 1 was loaded into a flask and heated to 50°C, after which 10 g of silane 2 in methanol was added dropwise within 30 minutes. The vacuum line switch was turned on. The mixture was stirred for 1 hour and then discharged.

[0149] The typical characteristics of this finished product were as follows: viscosity at 40°C 19,800 mPa·s; Gardner color 8; amine value 293 mg KOH / g.

[0150] Example 4

[0151] Step 1: All synthesis processes are the same as Step 1 of Example 1.

[0152] Step 2: 97 g of the reaction product from Step 1 was loaded into a flask and heated to 45°C. 3 g of vinylbenzyl chloride (VBC) was added within 20 minutes. A slight exothermic effect was observed. The reaction was maintained for several hours to ensure that all VBC was completely consumed.

[0153] Step 3: 80 g of the reaction product from Step 2 was loaded and heated to 60°C. 20 g of silane 2 in methanol was added within 30 minutes. The mixture was then stirred for 1 hour and discharged.

[0154] The typical characteristics of this finished product were as follows: viscosity at 40°C 31,289 mPa·s; Gardner color 9; amine value 287 mg KOH / g.

[0155] Example 5

[0156] Step 1: A 2000 mL 4-neck round-bottom flask was equipped with a vacuum line, a dropping funnel, a nitrogen outlet, and a stirrer. 460 g of dimeric acid and 225 g of Ancarmine® 2655 were loaded into the flask. The mixture was heated to 180°C under stirring to remove water. The temperature was raised to 240°C and the reaction was carried out for 2 hours. Water was removed. Subsequently, the vacuum line was switched on and nitrogen purging was stopped to reduce the pressure. The contents were cooled to 100°C. 100 g of Exol™ D80 was loaded into the mixture. The mixture was stirred for 1 hour and then cooled to 70°C.

[0157] Step 2: 95 g of the reaction product from Step 1 was loaded into a flask and heated to 50°C, after which 2.5 g of silane in methanol was added dropwise within 30 minutes. The vacuum line was switched on. The mixture was stirred for 1 hour and then discharged.

[0158] The typical characteristics of this finished product were as follows: viscosity at 40°C 17,350 mPa·s; Gardner color 8; amine value 310 mg KOH / g.

[0159] Example 6

[0160] Step 1: A 2000 mL 4-neck round-bottom flask was equipped with a vacuum line, a dropping funnel, a nitrogen outlet, and a stirrer. 460 g of dimeric acid and 240 g of tetraethylenepentaamine (TEPA) were charged into the flask. The mixture was heated to 180°C under stirring to remove water. The temperature was raised to 240°C and the reaction was carried out for 2 hours. Water was removed. Subsequently, the vacuum line was switched on and nitrogen purging was stopped to reduce the pressure. The contents were cooled to 100°C. 105 g of diisopropyl naphthalene (DINP) was charged into the mixture. The mixture was stirred for 1 hour and then cooled to 70°C.

[0161] Step 2: 93 g of the reaction product from Step 1 was loaded into a flask and heated to 50°C, after which 7 g of silane 3 was added dropwise within 30 minutes. The vacuum line switch was turned on. The mixture was stirred for 1 hour and then discharged.

[0162] The typical characteristics of this finished product were as follows: viscosity at 40°C 17,890 mPa·s; Gardner color 8; amine value 279 mg KOH / g.

[0163] Example 7

[0164] Step 1: A 2000 mL 4-neck round-bottom flask was equipped with a vacuum line, a dropping funnel, a nitrogen outlet, and a stirrer. The flask was filled with 460 g of dimeric acid, 102.1 g of Ancarmine® 2655, and 115 g of triethylenetetramine (TETA). The mixture was heated to 180°C under stirring to remove water. The temperature was raised to 240°C and the reaction was carried out for 2 hours. Water was removed. Subsequently, the vacuum line was switched on and nitrogen purging was stopped to reduce the pressure. The contents were cooled to 100°C. 125 g of diisopropyl naphthalene (DINP) was added to the mixture. The mixture was stirred for 1 hour and then cooled to 70°C.

[0165] Step 2: 86 g of the reaction product from Step 1 was loaded into a flask and heated to 50°C, after which 14 g of silane 3 was added dropwise within 30 minutes. The vacuum line was switched on. The mixture was stirred for 1 hour and then discharged.

[0166] The typical characteristics of this finished product were as follows: viscosity at 40°C 21,080 mPa·s; Gardner color 9; amine value 320 mg KOH / g.

[0167] test

[0168] To evaluate the improvement of adhesion to metal surfaces in PVC plastisol formulations, PVC plastisol formulations were prepared as exemplified in the table below. The amidoamine compositions prepared in Examples 1 to 7 were used as adhesion promoters.

[0169] Table 1 PVC Plastisol Formulations

[0170]

[0171] Adhesion to metal was evaluated by testing the products of Examples 1 to 7 on PVC plastisol at various baking cycles and various loading levels. Six metal panels were used for all tests, four of which were made of different aluminum alloys and two of which were made of different steel. The baking cycle varied depending on the temperature at which the PVC plastisol-coated surface was baked. The temperatures used herein included 120°C, 130°C, 140°C, and 150°C. The baking time was 30 minutes. In the case of adhesion tests on steel panels and CED panels, the loading levels of the products were generally low, so it was observed that they adhered more easily compared to those made of ordinary aluminum alloys.

[0172] Eight panels were used to demonstrate the adhesive performance of PVC plastisol formulations with varying levels of adhesion promoter compositions. Four were made of aluminum alloys 6061, 5052, 3003, and 5083. Two were made of cathodic electrodeposition coated LS-800 (Kansai Paint Co., Ltd.) and ES-27 (Axalta Coating Systems). Two were made of cold-rolled steel and Type 304 carbon steel.

[0173] In the table presenting the test results, various symbols indicate different levels of adhesive strength.

[0174] - Poor adhesion;

[0175] + Allowable adhesion;

[0176] ++ Excellent adhesive strength.

[0177] Table 2 Adhesion characteristics of panels made of various aluminum alloys

[0178]

[0179] Table 2 (Continuous) Adhesion characteristics for panels made of various aluminum alloys

[0180]

[0181] In the table above, it is observed that the adhesive strength improves as the baking temperature increases from 120℃ to 140℃.

[0182] In addition, as shown in the table above, it is observed that the adhesive strength improves as the loading level of the adhesion promoter in the PVC plastisol increases from 2% to 5%.

[0183] It is observed that the products of Examples 6 and 7 can have excellent adhesion to all various aluminum alloy surfaces tested, regardless of baking cycle and loading level, compared to the other products of Examples 1 to 5.

[0184] Table 3: Adhesion characteristics for panels made of two different electrode-deposited primer metals

[0185]

[0186] After a baking cycle at a baking temperature in the range of 120°C to 150°C, all products of Examples 1 to 7 produced excellent adhesion to two different CED panels at a very low loading level of 0.5% to 1% by weight of PVC plastisol.

[0187] Table 4: Adhesion properties for panels made of steel and carbon steel

[0188]

[0189] According to Table 4, carbon steel was found to have slightly weaker adhesion to the PVC plastisol formulation compared to steel at low loading levels under a baking temperature of 120°C. The products of Examples 6 and 7 exhibited excellent bonding to the substrate even at a low loading level of 0.5 wt%. As the baking temperature exceeded 130°C, all products of Examples 1 to 7 were able to produce acceptable adhesion to a substrate made of two steels.

[0190] Various aspects and embodiments are possible. Some of these aspects and embodiments are described herein. After reading this specification, a person skilled in the art will recognize that these aspects and embodiments are merely illustrative and do not limit the scope of this disclosure. Embodiments may be in accordance with one or more of the embodiments listed below.

[0191] The foregoing description is provided to enable a person skilled in the art to construct and use the present disclosure, and is provided in relation to the field of application and its requirements. Various modifications of preferred embodiments will be apparent to a person skilled in the art, and the general principles defined herein may be applied to other embodiments and fields of application without departing from the spirit and scope of the present disclosure. Accordingly, the present disclosure is not limited to the embodiments presented, but is intended to conform to the broadest scope consistent with the principles and features disclosed herein. In this regard, specific embodiments within the present disclosure may not represent all the benefits of the present disclosure as broadly considered.

Claims

Claim 1 As an amidoamine composition, i) a) at least one amide group or at least one imide group; and b) an amidoamine having at least one amino group; and ii) a hydrochloride of an aminosilane represented by formula (I): An amidoamine composition comprising, wherein R1 is a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group; R2 is an aliphatic chain having at least one carbon atom; and R3, R4, and R5 are independently a hydrocarbon radical having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an aryloxy group having 6 to 20 carbon atoms, or a 2-(2-butoxyethoxy)ethoxy group. Claim 2 In claim 1, R1 is a substituted alkyl group or a substituted aryl group having at least one nitrogen atom of the form -NH2, -NHR6, or -NR7R8, wherein R6, R7, and R8 is an amidoamine composition in which the alkyl group, substituted alkyl group, aryl group, or substituted aryl group is independently an alkyl group. Claim 3 An amidoamine composition according to claim 1, wherein R3, R4, and R5 are independently selected from methyl, ethyl, propyl, butyl, methoxy, ethoxy, propoxy, butoxy, or 2-(2-butoxyethoxy)ethoxy. Claim 4 The amidoamine composition of claim 1, wherein the amidoamine is a reaction product of a) one or more carboxylic acids and b) one or more amines having at least two amino groups. Claim 5 In paragraph 4, an amidoamine composition in which the carboxylic acid includes a dicarboxylic acid. Claim 6 An amidoamine composition according to claim 4, wherein the amine comprises one or more polyalkylene polyamines. Claim 7 The amidoamine composition of claim 1, wherein the amidoamine is a reaction product of a) one or more amines having a terminal primary amino group and b) one or more copolymers of an alpha-olefin and an unsaturated carboxylic acid anhydride. Claim 8 An amidoamine composition according to claim 7, wherein the amine is selected from aminomethylpiperazine, aminoethylpiperazine, aminopropylpiperazine, aminomethylimidazolidine, aminoethylimidazolidine, aminopropylimidazolidine, dimethylaminopropylamine, or dimethylaminopropylaminopropylamine. Claim 9 In claim 7, an amidoamine composition in which the alpha-olefin is an alpha-olefin having 2 to 20 carbon atoms. Claim 10 In claim 7, an amidoamine composition in which the unsaturated carboxylic acid anhydride is selected from maleic anhydride, itaconic anhydride, or citraconic anhydride. Claim 11 The amidoamine composition according to claim 1, further comprising an organic chloride. Claim 12 i) an amidoamine composition according to claim 1; and ii) an adhesive composition comprising a curable polymeric composition. Claim 13 An adhesive composition according to claim 12, wherein the curable polymeric composition comprises poly(vinyl chloride) or vinyl chloride copolymer. Claim 14 An adhesive composition in which the curable polymeric composition comprises an epoxy polymer in Clause 12. Claim 15 An adhesive composition comprising an additional plasticizer in Clause 12. Claim 16 An adhesive composition according to claim 12, further comprising one or more additives selected from fillers, reinforcing agents, adhesion promoters, toughening agents, defoaming agents, dispersants, lubricants, coloring agents, marking materials, dyes, pigments, IR absorbers, antistatic agents, anti-blocking agents, nucleating agents, crystallization accelerators, crystallization retardants, conductive additives, carbon black, graphite, carbon nanotubes, graphene, drying agents, release agents, leveling aids, flame retardants, separators, optical whitening agents, rheology additives, photochromic additives, softeners, anti-slip agents, stabilizers, metal glitter, metal-coated particles, porosity inducers, glass fibers, nanoparticles, flow aids, or combinations thereof. Claim 17 An adhesive composition according to claim 16, wherein the additive has a weight percentage of less than 90% based on the total weight of the adhesive composition. Claim 18 An adhesive composition according to claim 12, wherein the amidoamine composition has a weight percentage of less than 10% based on the total weight of the adhesive composition. Claim 19 An adhesive composition according to claim 18, wherein the amidoamine composition has a weight percentage of more than 0.5% and less than 8% based on the total weight of the adhesive composition. Claim 20 A method for preparing an amidoamine composition of claim 1, comprising: i) providing an amidoamine having at least one amide group and b) at least one amino group; ii) a hydrochloride of an aminosilane represented by formula (I); The method comprises the steps of: providing a hydrochloride of amidoamine and aminosilane to form an amidoamine composition, wherein R1 is a hydrogen atom, an alkyl group, a substituted alkyl group, an aryl group, or a substituted aryl group; R2 is an aliphatic chain having at least one carbon atom; and R3, R4, and R5 are independently a hydrocarbon radical having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an aryloxy group having 6 to 20 carbon atoms, or a 2-(2-butoxyethoxy)ethoxy group.

Citation Information

Patent Citations

  • Antifouling coating composition to be applied to wet surface

    JP1990001774A

  • Adhesion improver and production of imidoamine

    JP1995206926A

  • Vinyl chloride-based plastisol composition

    JP1996020697A

  • Adhesion promoter for plastisols

    JP2007527933A